TEARY EYES: VALUE JUDGEMENTS IN THE CAPTIONS OF CELEBRITIES REGARDING ISRAEL-PALESTINE WAR - Qothrunnada, Qonita; Hermin Oktavian, Nurrisda; Shabrina Alisya, Nanda; Intan Putri, Eppi; Nur Fitriana, Pravita; Nur Amirah, Fatimah; Nur Khoiriyah, Aisyah (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2025)
The Israeli-Palestinian conflict has gained significant global attention, with notable Hollywood celebrities expressing their support or disapproval via social media, particularly on Instagram. Despite Hollywood celebrities' evident influence on Instagram, their role in voicing their opinions concerning the Israeli-Palestinian conflict has not been extensively studied. This qualitative research examines how Hollywood celebrities employ Instagram posts to voice their opinions on the Israeli-Palestinian conflict. To achieve this aim, we employ the value judgments theory that Macagno propounded to reveal the value judgments in Hollywood celebrities' Instagram posts concerning the Israeli-Palestinian conflict. The value judgment theory identifies three strategies: habit, mentioning previous actions, and metaphor and comparison. Our research establishes that the value judgments expressed in Hollywood celebrities' Instagram posts mainly fall under the second strategy, which emphasizes the causal relationship between the historical underpinnings of the conflict and its current state. Nevertheless, the value judgments theory by Macagno is limited in revealing the exact meaning of profile pictures on Instagram. Thus, this study proposes using technoself theory as a guide to explore a new research area concerning the significance of profile pictures.